HIV/AIDS and Social Capital in a Cross-Section of Countries - David, Antonio C. (World Bank, Washington, DC, 2012)
This paper attempts to quantify the impact of the HIV/AIDS epidemic on social capital with cross-country data. It estimates reduced-form regressions of the main determinants of social capital controlling for HIV prevalence, institutional quality, social distance, and economic indicators using data from the World Values Survey. The results obtained indicate that HIV prevalence affects social capital negatively. The empirical estimates suggest that a one standard deviation increase in HIV prevalence will lead to a 1 percent decline in trust, controlling for other determinants of social capital. If one moves from a country with a relatively low level of HIV prevalence such as Estonia, to a country with a high level such as Zimbabwe, one would observe an approximate 8 percent decline in social capital. These results are robust in a number of dimensions and highlight the empirical importance of an additional mechanism through which HIV/AIDS hinders the development process.